Parts-feeding systems for assembly : organisation, logistics and automation - Faccio, Maurizio; Cohen, Yuval (Organisation, logistics and automation: Volume 35, Issue 1., 2015)
The aim of this e-book is to play the role of a catalyst in advancing the research of part logistics in assembly systems. This is achieved by presenting novel, high-quality papers investigating part logistics and part feeding in assembly systems. These papers include innovative methodologies and tools, new real-world case studies and innovative automation technologies. The issue covers the macro, facility and micro logistics issues and factors of the problem, and enables readers to grasp the various aspects of part supply in mixed model assembly systems.